Couples in treatment : techniques and approaches for effective practice - Weeks, Gerald R., 1948-; Fife, Stephen T., 1951- (New York ; London, UK : Routledge Taylor and Francis Group, 2014)
"This third edition of Couples in Treatment helps readers conceptualize and treat couples from multiple perspectives and with a multitude of techniques. The authors do not advocate any single approach to couple therapy and instead present basic principles and techniques with wide-ranging applicability and the power to invite change, making this the most useful text on integrative, systemic couple therapy. Throughout the book the authors consider the individual, interactional, and intergenerational systems of any case. Gerald Weeks' Intersystems Model, a comprehensive, integrative, and contextual meta framework, can be superimposed over existing therapy approaches. It emphasizes principles of therapy and can facilitate assessing, conceptualizing couples' problems, and providing helpful interventions. Couple therapists are encouraged to utilize the principles in this book to enhance their therapeutic process and fit their approach to the client, rather than forcing the client to fit their theory"--
"This third edition of Couples in Treatment helps readers conceptualize and treat couples from multiple perspectives and with a multitude of techniques. Gerald Weeks' Intersystems Model, a comprehensive, integrative, and contextual meta framework, can be superimposed over existing therapy approaches. Couple therapists are encouraged to utilize the principles in this book to enhance their therapeutic process and fit their approach to the client, rather than forcing the client to fit their theory"--
Includes bibliographical references and index.
Keywords: Marital psychotherapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General